Leishmanicidal and Immunomodulatory Activities of the Palladacycle Complex DPPE 1.1, a Potential Candidate for Treatment of Cutaneous Leishmaniasis - dos Santos, Isabela B.; da Silva, Danielle A. M.; Paz, Fabiana A. C. R.; Garcia, Daniel M.; Carmona, Adriana K.; Teixeira, Daniela; Longo-Maugéri, Ieda M.; Katz, Simone; Barbiéri, Clara L. (Frontiers in Microbiology, 2018)
In the present study the effect of the palladacycle complex DPPE 1.1 on Leishmania (Leishmania) amazonensis was evaluated. DPPE 1.1 destroyed promastigotes of L. (L.) amazonensis in vitro at nanomolar concentrations, whereas intracellular amastigotes were killed at drug concentrations 5-fold less toxic than those displayed to macrophages. L. (L.) amazonensis-infected BALB/c mice were treated by intralesional injection of DPPE 1.1. Animals treated with 3.5 mg/kg and 7.0 mg/kg of DPPE 1.1 showed a significant decrease of foot lesion sizes and a parasite load reduction of 93% and 99%, respectively, when compared to untreated controls. Furthermore, DPPE 1.1 was non-toxic to treated animals. The inhibition of cathepsin B activity of L. (L.) amazonensis amastigotes by DPPE 1.1 was demonstrated spectrofluorometrically by use of a specific fluorogenic substrate. Analysis of T-cells populations in mice treated with DPPE 1.1 and untreated controls was performed by FACS. IFN-gamma was measured in supernatants of lymphocytes from popliteal and inguinal lymph nodes isolated from treated and untreated mice and stimulated with L. (L.) amazonensis amastigotes extract and active TGF-β was evaluated in supernatants of foot lesions; both dosages were carried out by means of a double-sandwich ELISA assay. Mice treated with DPPE 1.1 exhibited a significant increase of TCD4+ and TCD8+ lymphocytes and IFN-gamma secretion compared to untreated animals, whereas a significant reduction of active TGF-β was observed in treated mice. These findings open perspectives to explore the potential of DPPE 1.1 as an additional option for the chemotherapy of cutaneous leishmaniasis.